Pintar con palabras en el Barroco español - Álvarez de Sotomayor, Isabel Dans (Rome and Iberia : Inspirations and Connections throughout History, 2021)
The object of this work is the study of a poetic procedure with grecolatin influence in the poetry of the Golden Age: the ékprahsis in the broad sense. Various examples of descriptions classified by genres from Lope de Vega, Gabriel Bocángel, Francisco de Quevedo and Francisco de Rioja are provided for this purpose. We should appreciate the relation between the arts and the richness of the ecphrasis at this time, maybe for the extension of the silva.